2006
DOI: 10.2170/physiolsci.rp000505
|View full text |Cite
|
Sign up to set email alerts
|

L-Arginine Supplementation Causes Additional Effects on Exercise-Induced Angiogenesis and VEGF Expression in the Heart and Hind-Leg Muscles of Middle-Aged Rats

Abstract: Abstract:The effects of dietary L-arginine supplementation on exercise-induced angiogenesis and VEGF expression were examined in male middle-aged (12 months old) Wistar rats. Exercise training lasted for six weeks at 20 m/min on a 0% gradient for 10-60 min/day. Rats in the L-arginine-treated groups drank water containing 2.5% L-arginine. According to histochemical identification of the capillary profile, in the soleus muscle the capillary-to-fiber (C:F) ratio showed a significantly greater value in the L-argin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 34 publications
2
17
0
3
Order By: Relevance
“…[20,21] Furthermore, Arg was suggested to promote angiogenesis, stimulate insulin secretion, promote osteoblast differentiation, and enhance collagen synthesis, which are critical for bone formation. [22][23][24] Based on these observations, we proposed that Arg could improve the solubility of DG, decrease its cytotoxicity against normal cells, and modify its biological activities. In this study, we successfully synthesized a water-soluble arginyl-diosgenin (Arg-DG) conjugate by coupling Arg with the extracted DG.…”
Section: Introductionmentioning
confidence: 99%
“…[20,21] Furthermore, Arg was suggested to promote angiogenesis, stimulate insulin secretion, promote osteoblast differentiation, and enhance collagen synthesis, which are critical for bone formation. [22][23][24] Based on these observations, we proposed that Arg could improve the solubility of DG, decrease its cytotoxicity against normal cells, and modify its biological activities. In this study, we successfully synthesized a water-soluble arginyl-diosgenin (Arg-DG) conjugate by coupling Arg with the extracted DG.…”
Section: Introductionmentioning
confidence: 99%
“…However, our results clash with these, corroborating more recent studies. Lin et al 15 , Suzuki 16 and Huang et al 17 analyzed body weight of Wistar rats with different ages, submitted to many different kinds of physical exercises and administration of L-arginine in variable quantities. Such investigations did not prove difference in body weight of the studied animals.…”
Section: Discussionmentioning
confidence: 99%
“…The oral ingestion of the L-arginine amino acid has been efficient in increasing the angiogenesis induced by physical exercise through increase of expression of the vascular endothelial growth factor (VEGF) 16 . Some authors have reported that the increase of the VEGF levels in patients results in increase of collateral arterial circulation 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Очень важными для представителей этого вида спорта являются также межмышечные и нервно-мышечные взаимодейст-вия [8,39]. В данном случае обеспечение прироста высота прыжка с места со штангой и высоты подъ-ема штанги в рывке в значительной степени связа-но с направленным влиянием L-аргинина [58], а, следовательно, и препарата на его основе -тивор-тин аспартата -на процессы в центральной и автономной нервной системах. Улучшение психо-физиологических характеристик спортсменов при курсовом приеме этого препарата является одним из опосредованных механизмов улучшения соревновательного результатов у представителей тяжелой атлетики [13,18], что обусловливает целесообразность применения тивортин аспартата в практике подготовки спортсменов.…”
Section: вплив 2-етил-6-метил-3-гідроксипіридину сукцинату на сітківкunclassified